Wit's End : Making Sense of the Great Movies. - Combs, James E. (Cambridge Scholars Pub., 2010)
This book is a study of the "Great Movies," that fluid category of feature films deemed by various authorities-film societies, critics, academics, and movie enthusiasts-to be the enduring and memorable works of cinematic history. But what are they about? In Wit's End, the author attempts to "make sense" of these films in order to understand their greatness in the context of their relation to other films and to the worlds they come from and recreate on screen. To that end, we employ the conce ...